PENINGKATAN KEPATUHAN WAJIB PAJAK USAHA KECIL MENENGAH MELALUI PELATIHAN PEMANFAATAN SISTEM INFORMASI PERPAJAKAN - Anggun Hilendri Lestari; Lalu Takdir Jumaidy; Tiallurra Della Nabila (Jurnal Abdimas Sangkabira, 2021)
This community service activity aims to train small and medium business owners in using the tax information system. The method used in carrying out this activity is training on the use of tax information systems accompanied by continuous assistance in the form of consultations if there is a problem in using the application in the system. Based on the results of community service, it can be concluded that community service partners have complied with their tax obligations by utilizing e-filling, which is one of the tax systems designed by the Directorate General of Taxes to make it easier for taxpayers to pay their taxes. In addition, the Directorate General of Taxes has upgraded its tax system and service partners have difficulty using it.